1992
DOI: 10.1017/s0033822200063864
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Influence on the 14C Activity and Other Constituents of Recent Lake Sediments: A Case Study1

Abstract: ABSTRACT. Anthropogenic activities that introduce an excess of nutrients and other pollutants into rivers and lakes are causing significant changes in their aquatic environment. Excessive nutrients greatly accelerate eutrophication, and lake marl formed during eutrophication differs from that formed in oligotrophic water.We analyzed recent sediment cores from Prone and Kozjak lakes located in Plitvice National Park, central Croatia.Analyses consisted of 14C activity of calcareous lake marl, the ratio of stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Pazdur, Pazdur & Szulc (1988) Several shallow sediment cores were retrieved from Lake Kozjak (see Fig. 1A) to study anthropogenic influences on lakes and lake sediments, as described by Srdoc et al (1992). The uppermost 9 cm of the core showed a non-linear increase of 14C activity compared to layers immediately below 9 cm.…”
Section: Dating the Organic Component Of Sedimentmentioning
confidence: 99%
“…Pazdur, Pazdur & Szulc (1988) Several shallow sediment cores were retrieved from Lake Kozjak (see Fig. 1A) to study anthropogenic influences on lakes and lake sediments, as described by Srdoc et al (1992). The uppermost 9 cm of the core showed a non-linear increase of 14C activity compared to layers immediately below 9 cm.…”
Section: Dating the Organic Component Of Sedimentmentioning
confidence: 99%
“…Moreover, the lakes are located in mostly deciduous forest, and huge amount of leaves are transported into the lakes every year. Anthropogenic influence on 14 C activity and some aliphatic and polycyclic aromatic hydrocarbons of recent lake sediment in lakes Kozjak and Prošće were published in Srdoč et al (1992). Additionally, some preliminary measurements of dissolved organic carbon (DOC) in water in this area showed that increase of DOC can disturb or even stop the process of tufa precipitation (Srdoč et al, 1985a).…”
Section: Introductionmentioning
confidence: 99%
“…Alongside diatoms, chrysophytes frequently constitute a significant component of phytoplankton assemblages of karst lakes (Srdoč et al, 1992;Morata et al, 2003;Gligora et al, 2007;Ž utinić et al, 2014;Gligora Udovič et al, 2015). The major representative, Dinobryon spp.…”
Section: Assemblage Analysesmentioning
confidence: 99%